2001
DOI: 10.1056/nejmoa010187
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy after Surgery Compared with Surgery Alone for Adenocarcinoma of the Stomach or Gastroesophageal Junction

Abstract: Postoperative chemoradiotherapy should be considered for all patients at high risk for recurrence of adenocarcinoma of the stomach or gastroesophageal junction who have undergone curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

66
2,271
18
111

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,117 publications
(2,466 citation statements)
references
References 21 publications
66
2,271
18
111
Order By: Relevance
“…However, the sensitivity analysis as performed in the current study suggests that the survival advantages of preoperative RT remained clinically Second, an important caveat of the current study is that the SEER database does not provide data regarding chemotherapy. However, both preoperative and postoperative RT are almost always administered concurrently with chemotherapy, [1][2][3][4][5]7,26,28 and therefore it is less likely that the lack of chemotherapy data is a source of bias in the concurrent setting. In addition, chemotherapy itself can be a possible cause of cardiopulmonary mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sensitivity analysis as performed in the current study suggests that the survival advantages of preoperative RT remained clinically Second, an important caveat of the current study is that the SEER database does not provide data regarding chemotherapy. However, both preoperative and postoperative RT are almost always administered concurrently with chemotherapy, [1][2][3][4][5]7,26,28 and therefore it is less likely that the lack of chemotherapy data is a source of bias in the concurrent setting. In addition, chemotherapy itself can be a possible cause of cardiopulmonary mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In the subset of patients with tumors of the gastroesophageal junction, CRT delivered postoperatively has also demonstrated a survival benefit. 7 To the best of our knowledge, no randomized controlled trials currently exist that compare the outcomes of the sequencing of CRT in relation to surgery in patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the chemotherapy arm only 43% of patients completed the postoperative planned programme, probably as a consequence of the fact that gastric cancer patients have been often shown to be hardly compliant to postoperative chemotherapy . On the other hand, it has also been previously reported that a chemoradiotherapy adjuvant approach may improve the outcome of radically resected gastric cancer by lowering the incidence of local relapse (Macdonald et al, 2001). The availability of various and different treatment options has consequently reintroduced the crucial question of an accurate treatment selection and a correct definition of high-risk categories, which may help identifying subgroups of patients benefiting more from additional medical treatments after (or before) radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although most clinical trials investigating adjuvant chemotherapy generated inconclusive results (Hermans et al, 1993;Earle andMaroun, 1999, Cascinu et al, 2005), it has been reported that a chemoradiotherapy adjuvant approach may improve the outcome of radically resected gastric cancer by lowering the incidence of local relapse (Macdonald et al, 2001).…”
mentioning
confidence: 99%
“…Treatment results of advanced gastric cancer have been improved by the introductions of lymph node dissection and postoperative adjuvant chemotherapy and radiation therapy [1][2][3]. However, more than 50% of potentially curable advanced gastric cancer patients died of peritoneal recurrence [4].…”
Section: Introductionmentioning
confidence: 99%